Diagnosing breast carcinoma in young women. Issue 6777 (16th March 1991) - Yelland, A; Graham, M D; Trott, P A; Ford, H T; Coombes, R C; Gazet, J C; Polson, N G
Abstract : OBJECTIVE–To assess the individual and combined diagnostic accuracy of clinical examination, mammography, and fine needle aspiration biopsy in young women with breast cancer. DESIGN–Analysis based on case notes of patients presenting with breast cancer during 1971-89. SETTING–A combined breast clinic. PATIENTS–Consecutive series of 81 women aged less than 36 with histologically proved breast cancer presenting with a discrete mass over 19 years. MAIN OUTCOME MEASURES–Results of clinical examination, xeromammography or conventional mammography, fine needle aspiration biopsy, and examination of tissue removed by surgery. RESULTS–The clinical diagnosis was correct in 47 women and radiography in 35. Fine needle aspiration biopsy was correct in 47 of the 63 women in whom it was successfully performed. Fine needle aspiration was significantly more accurate than mammography (78% v 45%, p less than 0.01). Ten (16%) patients had negative results on clinical examination, mammography, and fine needle aspiration. CONCLUSION–Mammography alone seems inadequately sensitive to detect breast cancer in young patients. When all investigations give negative results excision biopsy is the only way of obtaining a definitive diagnosis.